1999
DOI: 10.1002/(sici)1097-0215(19990105)80:1<1::aid-ijc1>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase components as a diagnostic tool in human oral lesions

Abstract: Telomerase activity is considered to be a diagnostic marker of malignancy since most malignant cells express this activity and most somatic cells do not. However, the detection of telomerase activity is rather complicated and is affected by many factors. Recently, human telomerase components were cloned and found to consist of 3 subunits. We assessed which component of telomerase best correlates with malignancy in order to study the possibilities for developing a new diagnostic marker. Telomerase activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 16 publications
3
42
1
Order By: Relevance
“…2). These findings are in accordance with the results of previous studies of telomerase components in other malignant tumors (14,26,27).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2). These findings are in accordance with the results of previous studies of telomerase components in other malignant tumors (14,26,27).…”
Section: Discussionsupporting
confidence: 93%
“…mRNA expression of telomerase components in salivary gland tissues has been scarcely investigated (22,26). In the present study, hTERT mRNA was highly expressed in malignant tumors and correlated with the telomerase activity.…”
Section: Discussionmentioning
confidence: 56%
“…For these reasons, we analysed the telomerase activity of our samples using the TRAP method. Although the telomerase activity levels cannot be considered as quantitative due to the exponential nature of the PCR amplification, we and others (Sumida et al, 1999;Haik et al, 2000) have consistently shown that differences in telomerase activity levels can be shown reproducibly using the TRAP assay. Therefore we felt entitled to split telomerase-positive lesions in two groups of high and low level of expression depending on the increase of absorbance.…”
Section: Discussionmentioning
confidence: 61%
“…Telomerase activity correlates with levels of hTERT messenger RNA (Kyo et al, 1999;Sumida et al, 1999;Shamanin et al, 2008), which is the rate-limiting determinant of the enzymatic activity of telomerase (Kyo et al, 1999). Consequently, we measured hTERT messenger RNA levels using quantitative reverse transcriptase-PCR (Kirkpatrick et al, 2004 based on sensitive and specific Taqman chemistry previously optimized in our laboratory (DeCarlo et al, 2008).…”
Section: Resultsmentioning
confidence: 99%